2020
DOI: 10.1162/jocn_a_01609
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Control of Task Selection Does Not Eliminate the Impact of Selection History on Attention

Abstract: The human visual system can only process a fraction of the information present in a typical visual scene, and selection is historically framed as the outcome of bottom–up and top–down control processes. In this study, we evaluated how a third factor, an individual's selection history, interacts with top–down control mechanisms during visual search. Participants in our task were assigned to one of two groups in which they developed a history of either shape or color selection in one task, while searching for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 79 publications
2
8
0
Order By: Relevance
“…The task-switching literature has shown that voluntary choice designs in which participants choose what they will respond to, allow for optimal task set preparation when compared to trial-by-trial cuing paradigms (Arrington & Logan, 2005;Chen & Hsieh, 2015). This was confirmed with a comparison of a cuing and a voluntary choice variant of matched attention capture tasks, using the pre-stimulus CNV component as an index of proactive task set preparation (Henare et al, 2020). In contrast to the cuing task, results showed more pre-stimulus activation in the voluntary task that was also unaffected by intertrial factors.…”
Section: Commentarymentioning
confidence: 77%
See 2 more Smart Citations
“…The task-switching literature has shown that voluntary choice designs in which participants choose what they will respond to, allow for optimal task set preparation when compared to trial-by-trial cuing paradigms (Arrington & Logan, 2005;Chen & Hsieh, 2015). This was confirmed with a comparison of a cuing and a voluntary choice variant of matched attention capture tasks, using the pre-stimulus CNV component as an index of proactive task set preparation (Henare et al, 2020). In contrast to the cuing task, results showed more pre-stimulus activation in the voluntary task that was also unaffected by intertrial factors.…”
Section: Commentarymentioning
confidence: 77%
“…In the categorization task, they categorized either a colour or shape singleton depending on group assignment. In the voluntary version of the experiment (Henare et al, 2020) participants performed the exact same tasks except that prior to trial initiation, they made an un-speeded decision about whether they would do a search trial or categorization trial. These data provide two main avenues for analysis.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…One special form of selection history has been investigated in [1,6,7]. These studies combined an associative learning task with a visual search task.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we introduce an algorithmic-level model (in the sense of Marr [31]) to show how bottom-up, top-down and selection history compete against each other to guide visual attention toward a specific target. By selection history we mean the effect of learning from previous experience on the current task (see [1,6,7]). The model comprises priority maps to integrate goal-driven, saliency-based and history-related biases in a winner-take-all manner.…”
Section: Introductionmentioning
confidence: 99%